Edge-carboxylated graphene nanoplatelets as efficient electrode materials for electrochemical supercapacitors. (February 2019) - Deb Nath, Narayan Chandra; Jeon, In-Yup; Ju, Myung Jong; Ansari, Sajid Ali; Baek, Jong-Beom; Lee, Jae-Joon
Abstract: Edge-carboxylated graphene nanoplatelets (ECG ), prepared by a mechano-chemical reaction (or ball milling method) in the presence of dry ice, are eligible for an efficient electrode materials for electrochemical supercapacitors. ECG contained a higher content of edge-carboxylic groups with less structural defects, compared with the nitrogen-doped carboxylic graphene (NGOOH ) prepared from the conventional solution-exfoliation of graphite. The structural defects level of ECG is ca . 16.2%, while it was ca . 48.9% for NGOOH . The edge-carboxylation increases the electroactive surface area, hydrophilicity and wettability of graphene without serious deterioration of the intrinsic properties e.g ., chemical, mechanical and electronic properties. In result, it is more effective in enabling ion adsorption and rapid electrolyte diffusion within the pores of graphene which results in a significant increase of specific capacitance ( C sp ) to 365.72 F/g at a current density of 1 A/g, with a good charge–discharge property and rate capability for ECG. On the other hand, the C sp significantly decreases to ca. 175.05 F/g for NGOOH, as its high level of structural defects seriously affected its electronic properties. Graphical abstract: Image 1